Implementation of Case-Based Learning in 1st-Year MBBS Students -Future of Medical Professionals Learning Methods in Indian Medical Colleges? - Mandar Vilas Ambike; Jayshree Sachin Kharche; Shraddha Shripad Kulkarni; T Vijaya Sagar; K Vijayakumar; Suresh Babu Kondaveeti (Journal of Pharmacy and Bioallied Sciences)
Background: Case Based Learning (CBL) is the best method for correlation of knowledge with clinical scenarios. The present study is planned to implement case-based learning in 1st-Year MBBS students and find out the perception of the students as a guideline to incorporate this activity in the curriculum. Material and Methods: The study was conducted among 1st-Year MBBS students. The students who consented to participate were divided into 23 groups each containing 5-6 participants. The case along with the reference material was allotted to the groups of students sequentially. Faculty was allotted to each group of students for their help and discussion on the given case. The completed activity was uploaded on Moodle for all the students to go through. After 25 weeks, students’ perception of the activity were obtained with the help of validated questionnaire through Google Forms. Data was analyzed in SPSS software. Results: 85% of students felt that CBL helped them understand clinical applications, enhanced problem-solving skills and retention of knowledge. More than 85% of students were comfortable with CBL in terms of relevance to the curriculum, mode of conduction, and development of interest. Over 90% of students mentioned that provided resources and faculty were helpful. Conclusion: The study concludes that successful implementation of case-based learning is possible for 1st-Year MBBS medical students. Students perceived CBL as a motivating and effective teaching-learning method.